2018
DOI: 10.1016/j.chiabu.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Developing a tailored substance use intervention for youth exiting foster care

Abstract: Youth who are aging out of the foster care system face significant barriers to accessing substance use treatment. Mobile interventions have shown efficacy for several mental and physical health issues and may be helpful in overcoming barriers facing foster youth with substance use problems. A program (iHeLP) for substance use reduction was developed that used a computerized screening and brief intervention (SBI) followed by six months of dynamically-tailored text messages. The program was shown to focus groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 51 publications
1
13
0
2
Order By: Relevance
“…Our finding that the ratings were not significantly different suggests that our nonthreatening intervention tool may have an important advantage over traditional approaches. Results from the exit interviews further support this interpretation, as satisfaction with the text messaging component mirrored our previous quantitative work in this area, where youth exiting care were highly supportive of using mobile phones to deliver intervention content (Braciszewski, Tzilos Wernette, et al, 2018). In addition, participants suggested that we offer iHeLP for longer than six months and extend care beyond the text messages to contact with other peers or professionals.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Our finding that the ratings were not significantly different suggests that our nonthreatening intervention tool may have an important advantage over traditional approaches. Results from the exit interviews further support this interpretation, as satisfaction with the text messaging component mirrored our previous quantitative work in this area, where youth exiting care were highly supportive of using mobile phones to deliver intervention content (Braciszewski, Tzilos Wernette, et al, 2018). In addition, participants suggested that we offer iHeLP for longer than six months and extend care beyond the text messages to contact with other peers or professionals.…”
Section: Discussionsupporting
confidence: 68%
“…Participants had strongly positive feelings about the texting component, stating that it made them think, built motivation, was easy to use, and felt like someone else was caring about their health. New iHeLP components suggested in our previous open trial (biweekly goal reminders and weekly feedback on substance use; Braciszewski, Tzilos Wernette, et al, 2018) were very well received. All participants indicated that the goal reminders were helpful to keep on track and that feedback on progress was empowering and provided specific motivation for not smoking marijuana.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Since we are hoping to recruit a sample of smokers from the general population, recruitment methods include posting advertisements online on social media websites such as Craigslist or Facebook, as well as through flyers targeted at a variety of venues including pharmacies, grocery stores, and churches. These methods have proven successful in our previous studies [37,41,42]. In addition, we will be reviewing the hospital's electronic health records for patients who tentatively match the eligibility criteria (i.e.…”
Section: Recruitment and Screeningmentioning
confidence: 99%